Application of The Change Point Analysis to The Long-Term Restoration of CD4 Count Among Well-Controlled HIV-1 Infected Patients Who Started Antiretroviral Therapy. (4th October 2017) - Yoshikazu, Mutoh; Nishijima, Takeshi; Tanaka, Noriko; Inaba, Yosuke; Kikuchi, Yoshimi; Gatanaga, Hiroyuki; Oka, Shinichi
Abstract: Background: Although CD4 count is an important marker for prognosis of patients infected with HIV-1, how long and how much CD4 count will increase after initiation of cART are still unknown. Hence, the aim of this study is, using change point analysis, to examine the long-term CD4 count restoration among well-controlled HIV-1 patients. Methods: In this single-center cohort study at AIDS Clinical Center, Tokyo, we examined HIV-1 infected patients who initiated cART between January 2004 and January 2012 and achieved HIV viral load of <200 copies/mL within first 48 weeks of treatment and maintained viral suppression (VL <200 copies/mL) for at least 4 years. cART was defined as combination regimen which consisted of NNRTI, PI, or INSTI, plus two NRTIs. All patients were followed until censoring (defined by VL >200 copies/mL, discontinuation of cART for >30 days, lost to follow-up for >1 year, initiating chemotherapy for malignancy, or death), or at end of the observation period (September 30, 2015). Change point analysis was performed to determine the time point where the restoration of CD4 count becomes plateau. Results: Of 752 patients, 708 (94.2%) were male and 89.9% was MSM. The median age was 39.3 years [IQR, 32–45] and the median baseline CD4 count and %CD4 were 172 cells/mm 3 [IQR, 61–254], and 13.8% [IQR, 7.7–18.5], respectively. The median follow-up period was 87.0 months [IQR, 65.2–109.2] and 134 were followed over ten years. With change point analysis, both longitudinal increase of CD4 count and %CD4 increased linearly until 78.6 and 62.2 months, respectively. Stratified by baseline CD4 count (<200 cells/mm 3, 200–350 cells/mm 3, and >350 cells/mm 3 ), CD4 count increased linearly until 76.2, 62.4, and 58.6 months, respectively. Moreover, the percentage of patient who achieved 500 cells/mm 3 during study period was 63.5%, 87.2%, and 92.0%, respectively. Conclusion: With change point analysis, restoration of CD4 count and %CD4 continued increasing linearly until 6.5 and 5 years of cART, respectively. Patients with lower baseline CD4 count showed longer CD4 count recovery than those with higher baseline CD4; however, their CD4 count did not recover as high as those with higher baseline CD4 count. Disclosures: All authors: No reported disclosures.